The shaping of legal consciousness through the experience of short-term incarceration - Masiangoako, Puleng Thato (My University, 2018)
While being home to one of the greatest constitutions in the world, South Africa is also notorious for brutal policing practices, endemic corruption, and an overstrained criminal justice system. This apparent gap between the normative conceptions of the law and the actual experiences of being subjected to the criminal justice system forms the crux of this study. This study explores how community activists, student activists, and migrants in Johannesburg, who rely on the law for protection and effective political expression and participation, understand the law through their experiences of arrest and short-term incarceration. This work introduces the concept of legal consciousness to the South African context, whilst also drawing heavily from South African literature of the law and criminal justice system. This research is grounded in the experiences of arrest and pre-trial and immigration detention shared by these individuals, which are used to develop a rich account of legal consciousness in South Africa. It also sheds light on some of the ways in which the criminal justice system sustains its legitimacy within a post-apartheid framework despite the gaps between what the law ought to be and what the law actually is. Very broadly, the study argues that these groups experience and understand the law in terms of their socio-political identities. Furthermore, their efforts to rationalize their experiences of arrest and detention serve to reconcile the gap between what the law is and what the law should be, thus unintentionally contributing to the reinforcement of legal hegemony. These experiences of the law and criminal justice system call into question the core constitutional values of equality and dignity.
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master of Arts in Politics to the University of the Witwatersrand’s Faculty of Humanities, March 2018
Keywords: Criminal justice, Administration of--South Africa; Prison sentences--South Africa; Corrections--South Africa